Electroluminescent Display with Picture Storage - Z. Porada; E. Schabowska-Osiowska (Active and Passive Electronic Components)
Memory cells, composed of PC and EL thin film elements, have been utilized to designing of a display with picture storage. Such a picture storing electroluminescent display may prove competitive with used now picture storing methods in the digital form. A mathematical model suitable for analysing the properties of a PC-El system is proposed and the preparation of PC and EL thin film elements is described. For a single pixel the dependences of output signal on the time for various values of amplitude and frequency of supplying voltage are presented.